2018
DOI: 10.2147/copd.s166902
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between obstructive lung disease and non-alcoholic fatty liver disease in the Korean population: Korea National Health and Nutrition Examination Survey, 2007–2010

Abstract: PurposePrevious studies have shown that progressive forms of non-alcoholic fatty liver disease (NAFLD) occur frequently in patients with obstructive lung disease (OLD). However, few studies have written about this relationship. This study aimed to investigate the relationship between OLD and NAFLD.Subjects and methodsThe Korea National Health and Nutrition Examination Survey is a national population-based, cross-sectional surveillance program that was initiated to assess the health and nutritional status of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
3
24
1
Order By: Relevance
“…The ECLIPSE data show a similar liver density distribution between COPD and controls. Our results are at variance with previous studies where the prevalence of steatosis ranging from 30% to 41% was reported in COPD 24,25 and found to be higher than the reported 5% to 20% prevalence in the general population. 17,29,30 These discrepancies are likely related to the use of different diagnostic tools across studies, including biological scores and transient elastography 31 which have the ability to detect milder fatty infiltration compared to CT scan.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The ECLIPSE data show a similar liver density distribution between COPD and controls. Our results are at variance with previous studies where the prevalence of steatosis ranging from 30% to 41% was reported in COPD 24,25 and found to be higher than the reported 5% to 20% prevalence in the general population. 17,29,30 These discrepancies are likely related to the use of different diagnostic tools across studies, including biological scores and transient elastography 31 which have the ability to detect milder fatty infiltration compared to CT scan.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the potential two-way relationship between COPD and liver steatosis due to chronic low-grade inflammation, intermittent hypoxia and induced adipokines, 24,25 few data are available to draw an epidemiologic picture of liver steatosis in this population. In a previous study, 26 we reported that the liver fibrosis stage of non-alcoholic fatty liver disease, but not steatosis, is an independent factor of cardiovascular morbidity in COPD, in line with results in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies are now beginning to investigate the possible relationship between lung disease and NAFLD. One such study among a Korean population found that those with NAFLD were 33% more likely to have obstructive lung disease (OLD) and those with OLD were 55% more likely to have NAFLD after adjusting for age, sex, and smoking history . Another study found similar results that, despite the presence or nonpresence of smoking, the incidence of NAFLD in those with OLD increased .…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, several studies reported a significant association between NAFLD and decreased lung function in the general population. [3][4][5][6][7] However, detailed underlying mechanisms still remain unresolved.…”
Section: Introductionmentioning
confidence: 99%